Capacity development for urban water senior staff members, stakeholders and influencers in Accra Metropolitan Assembly (AMA) and Sekondi- Takoradi Metropolitan Assembly (STMA) in Ghana - Agbenyegah, George Kwasi (Open Science Journal, 2020)
It is expected that adequate quantity and quality of service delivery is one of the preconditions that contributes to safe water and sanitation delivery. Yet the human resource gap in WATSAN sector is relatively unknown (S. Cavill & D. Saywell, 2009). This paper outlines a piece of research that was conducted to provide a reliable skill gap assessment and building solution in Ghana to national water utility provider staff members, stakeholders and influencers. The Purpose of the Research is to undertake Training Needs Analysis that will be followed up with Capacity Gap Assessment and Enhancement in urban water management and service delivery in Accra and Sekondi- Takoradi Metropolitan Assembly, Ghana The research found significant relationship between staff, stakeholders and influences service quality delivery and customer satisfaction. Therefore, the study was followed up with staff, stakeholders and influencer’s capacity building initiatives and motivation techniques, communication skills, cost reduction strategies, assets maintenance, billing cycles, monitoring and evaluation as panacea to quality service delivery. Furthermore, the study recommended that the management, influencers and stakeholders should reexamine and re programme the organization’s conceptual framework, vision, mission and operations such as their customer data base system to capture their customer’s profiles and needs so as to deliver customer focused services. Key Words: WATSAN, Utility, Influencers, Service Delivery, Customer, Staff, Stakeholders, Capacity, Ghana